2014
DOI: 10.1016/j.jebo.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Why are educated and risk-loving persons more mobile across regions?

Abstract: Why Are Educated and Risk-Loving PersonsMore Mobile Across Regions? * Why are better educated and more risk-friendly persons more mobile across regions? To answer this question, we use micro data on internal migrants from the German SocioEconomic Panel (SOEP) 2000-2006 and merge this information with a unique proxy for region-pair-specific cultural distances across German regions constructed from historical local dialect patterns. Our findings indicate that risk-loving and skilled people are more mobile over l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 27 publications
2
67
0
Order By: Relevance
“…Previous tests document the relationship of risk and migration. Among skilled people, those who are less risk averse are more willing to migrate to culturally different regions in Germany (31). Research on expatriate networks and international migration timing suggests that as the size of expatriate networks increases over time, finding employment after migration becomes less uncertain, inducing more risk-averse individuals to migrate (32).…”
Section: Previous Research On Staying and Duration Of Residencementioning
confidence: 99%
“…Previous tests document the relationship of risk and migration. Among skilled people, those who are less risk averse are more willing to migrate to culturally different regions in Germany (31). Research on expatriate networks and international migration timing suggests that as the size of expatriate networks increases over time, finding employment after migration becomes less uncertain, inducing more risk-averse individuals to migrate (32).…”
Section: Previous Research On Staying and Duration Of Residencementioning
confidence: 99%
“…While issues of risk and mobility are receiving growing attention in the mobility literature (e.g., Bauernschulster et al 2014), almost all empirical studies which attempt to incorporate risk do so using proxies, as captured in responses to questions on hypothetical actions or responses to hypothetical investment decisions. While they may (or may) not be transferable measures either across realms or over time, these proxies have no observable reference point.…”
Section: One Might Be Tempted To Conclude That Even If Prospect Theomentioning
confidence: 99%
“…In their study on the relationship between fertility intention and residential mobility, Ermisch and Steele (2016) found that women's educational qualification has no significant effect on residential mobility in the mobility model and included the variable in the fertility intention model as one of the excluded covariates. Women's education is more relevant in long-distance moves (e.g., job-related moves) than shortdistance moves (e.g., fertility-related moves; Bauernschuster, Falck, Heblich, Suedekum, & Lameli, 2014;Clark, 2013;Van Ommeren, Rietveld, & Nijkamp, 1997). Moreover, some studies suggest that women's education may be irrelevant to mobility when other variables that are highly correlated with education are included (Quigley & Weinberg, 1977) or when husbands' contribution to family income is large (Lichter, 1982).…”
Section: Residential Mobilitymentioning
confidence: 99%